Psychosocial interventions for disruptive behaviour problems in children in low‐ and middle‐income countries: a systematic review and meta‐analysis - Burkey, Matthew D.; Hosein, Megan; Morton, Isabella; Purgato, Marianna; Adi, Ahmad; Kurzrok, Mark; Kohrt, Brandon A.; Tol, Wietse A. (Journal of child psychology and psychiatry, 2018)
Background Most of the evidence for psychosocial interventions for disruptive behaviour problems comes from Western, high‐income countries. The transferability of this evidence to culturally diverse, low‐resource settings with few mental health specialists is unknown. Methods We conducted a systematic review with random‐effects meta‐analysis of randomized controlled trials examining the effects of psychosocial interventions on reducing behaviour problems among children (under 18) living in low‐ and middle‐income countries (LMIC). Results Twenty‐six randomized controlled trials (representing 28 psychosocial interventions), evaluating 4,441 subjects, met selection criteria. Fifteen (54%) prevention interventions targeted general or at‐risk populations, whereas 13 (46%) treatment interventions targeted children selected for elevated behaviour problems. Most interventions were delivered in group settings (96%) and half (50%) were administered by non‐specialist providers. The overall effect (standardized mean difference, SMD) of prevention studies was −0.25 (95% confidence interval (CI): −0.41 to −0.09; I2: 78%) and of treatment studies was −0.56 (95% CI: −0.51 to −0.24; I2: 74%). Subgroup analyses demonstrated effectiveness for child‐focused (SMD: −0.35; 95% CI: −0.57 to −0.14) and behavioural parenting interventions (SMD: −0.43; 95% CI: −0.66 to −0.20), and that interventions were effective across age ranges. Conclusions Our meta‐analysis supports the use of psychosocial interventions as a feasible and effective way to reduce disruptive behaviour problems among children in LMIC. Our study provides strong evidence for child‐focused and behavioural parenting interventions, interventions across age ranges and interventions delivered in groups. Additional research is needed on training and supervision of non‐specialists and on implementation of effective interventions in LMIC settings.